Policing hate crimes in Bosnia and Herzegovina - Lalić, Velibor (Policing and society, 2018)
Studying hate crimes in a country divided along sectarian lines, such as Bosnia and Herzegovina, presents a substantial challenge for researchers. The consequences of hate crimes are multifaceted, and in an environment of institutional crime-control mechanisms that are still developing, these events can negatively affect society at large. Hate crimes often lead to ethnic and religious homogenisation, polarisation, intolerance, overt hatred and violence. This paper provides an overview of research findings relevant to policing hate crimes in post-conflict Bosnia and Herzegovina. Special focus is placed on policing at three levels: government policy (strategies for action at the level of the interior ministries), police policy (the implementation of action strategies in lower organisational units) and police practice (police fieldwork). The study is primarily based on a qualitative approach including interviews, observations and secondary data analyses. The general findings indicate that crime control is inadequate and influenced by an apparent lack of political will to tackle the problem. Our findings also revealed the absence of any systematic approach to deal with hate crimes, which implied numerous problems in policing at all levels. Bosnia and Herzegovina, as a transitional post-conflict country, has a long way ahead in establishing law enforcement institutions that will enable the rule of law, protect human rights and ensure political accountability.